Divine Inversion and Visual Hermeneutics: Rereading David and Goliath in 1 Samuel 17 - Sugihyono, Sugihyono (Journal of Comprehensive Science, 2025)
This article explores a narrative-visual hermeneutic approach to the story of David and Goliath in 1 Samuel 17:1–58, emphasizing the interpretive power of visualization in biblical exegesis. Traditional interpretations often focus on historical or theological dimensions, yet they tend to overlook how visual imagination and narrative construction shape reader engagement and theological understanding. Drawing upon cognitive literary theory, narrative criticism, and theological aesthetics, this study analyzes how descriptive details, rhetorical contrast, and spatial dynamics create a vivid mental simulation that reveals deeper theological motifs such as divine reversal, embodied faith, and covenantal trust. The research demonstrates that visualization not only enhances comprehension of the narrative structure but also reinforces its theological message—highlighting the triumph of divine agency through unlikely vessels. Through a detailed textual analysis, supported by contemporary biblical scholarship and visual-cognitive frameworks, the study affirms the value of imaginative engagement as a legitimate and transformative tool in biblical interpretation. This approach contributes to interdisciplinary conversations on hermeneutics, pedagogy, and the cognitive impact of Scripture.